(untitled) (The Strategic Review for Southern Africa, 2020)
Since achieving independence in June 1960, the Democratic Republic of Congo (DRC) has been grappling with the question of the citizenship of Kinyarwanda and Kirundi-speaking populations settled on its territory at different historical periods, herein referred to as the Banyarwanda. While there is evidence of the presence of some Banyarwanda communities on current Congolese territory prior to the advent of Belgian colonisation in the area, the majority of the Banyarwanda currently living in the DRC are descendants of those brought into the country through colonial immigration and labour recruitment processes, political exile and refuge as well as clandestine migration. Using a historical perspective, this article analyses the manner in which the question of the citizenship of the Banyarwanda has been handled in the DRC since the establishment of the Congo Free State in 1885. The article locates the roots of the problem in the poorly designed colonial policies surrounding the relocation of these populations to the Kivu region. However, the article acknowledges that the sole shortcomings on the part of colonial authorities would have never had the current consequences if it was not for the inconsistencies of the different post-colonial governments that have ruled over the DRC. Instead of resolving the citizenship question in an effective and sustainable manner, all these governments have based their respective responses to the issue on short-term political expediencies as dictated by the balance of forces within the country, the Kivu area and the Great Lakes region at a particular juncture.